Conspicuous and frank dilated vascular spaces: A marker of malignant transformation in oral submucous fibrosis - Sachin C. Sarode; Gargi S. Sarode; Namrata Sengupta; Urmi Ghone; Shankargouda Patil (Elsevier, 2021)
Histo-morphological alterations observed at mucosal surgical margins can be envisaged as potential markers of malignant transformation. In this paper, we have presented a very striking observation at the mucosal surgical margins of oral squamous cell carcinoma arising in the background of oral submucous fibrosis (OSCC-OSMF). Out of 38 cases of OSCC-OSMF, 22 (57.89%) showed conspicuous large dilated vascular spaces lined by endothelial cells in the background of dense fibrosis. These large dilated areas were engorged with red blood cells and were located at the juxta-epithelial and submucosal regions. Since surgical margin tissues are biologically close to malignant transformation, we proposed this unique feature as a potential predictive marker for oral submucous fibrosis that will aid in the early detection of OSCC. Future cohort studies are warranted to prove the authenticity of the present observations.